2020
DOI: 10.21203/rs.3.rs-72181/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial and Transconjugants Characteristics of Sul3 Positive Escherichia Coli Isolated from Animals in Nanning, Guangxi Province

Abstract: Background: Sulfonamides is the second most popular antibiotic in many countries, which leads to the widespread emergence of sulfonamides resistance. Sul3 is a late sulfanilamide resistance gene, whose research is relatively little. Result: 46 sul3 positive E. coli strains were separated. A total of 12 ST types were observed, and 1 of those was previously unknown type. The ST350 is the most numerous type. All isolates were multidrug-resistant E. coli, with high antimicrobial rates to penicillin, ceftriaxone so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Unlike the relatively low compressive strength of CAC, CAC exhibits a tensile strength close to or higher than that of NAC (Li, 2012; Wu et al, 2018). As the surface of coral aggregates is rough and porous, the mechanical interlock between the aggregates and the cement matrix at the interface is enhanced.…”
Section: Mechanical Propertiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Unlike the relatively low compressive strength of CAC, CAC exhibits a tensile strength close to or higher than that of NAC (Li, 2012; Wu et al, 2018). As the surface of coral aggregates is rough and porous, the mechanical interlock between the aggregates and the cement matrix at the interface is enhanced.…”
Section: Mechanical Propertiesmentioning
confidence: 87%
“…Therefore, the interface transition zone in the hardened cement matrix becomes denser and has less voids (Xu et al, 2019), as shown in Figure 3(b). Consequently, the microhardness in the interface transition zone is significantly higher than that of the coral aggregates itself and the cement matrix, and higher than that of normal aggregate concrete (NAC) (Li, 2012; Zhang, 2012). This feature also influences the long-term strength of CAC, which will be discussed later.…”
Section: Coral Aggregatesmentioning
confidence: 99%
“…The deviatoric-plane curves adopt an elliptic curve of William-Warnke 46 0 < θ < 60 to describe the intensity envelope, such as Equation (9) shows: where…”
Section: Failure Criterionmentioning
confidence: 99%
“…[4][5][6] The coral aggregates are mainly composed of CaCO 3 and are characterized by large porosity, high water absorption, and low strength, which makes more water required in the preparation of concrete to meet the requirements of strength and workability, while the aggregate itself is brittle and therefore generally not easy to prepare a higher strength concrete. [7][8][9][10][11][12] The CAC has the characteristics of early strength development fast, which is shown by the 7d compression strength can reach 80% of the 28d. 13,14 The long-term strength of CAC can still maintain a high level and can meet the requirements of engineering, but the main reason why the application of CAC is limited at present is the corrosion caused by adverse effects of chloride ions in seawater and coral aggregate on corrosion of concrete structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation